MODEL DISCOVERY LEARNING PADA PEMBELAJARAN IPA DALAM MENINGKATKAN BERPIKIR KRITIS SISWA - Emi Zulfa Faridah; Ardy Pujangga (INCARE, International Journal of Educational Resources, 2024)
The teaching and learning process between teachers and students can run well with a learning model that can support these learning activities. One of the learning models that can hone students' critical thinking and support the learning process is the discovery learning model. In implementing it, the teacher needs to choose a learning model that can be used as an alternative so that it is suitable for the situations and conditions being faced by students such as in learning science. The aim of this research was to find out the application of discovery learning as well as the factor in increasing the critical thinking of grade 6 students at SDN 2 Gadingkembar. This study used descriptive qualitative method. The procedure for collecting data is in a natural setting and the procedure for collecting data is through interviews, observation and documentation. The process of analyzing data obtained by researchers in the field begins with the stages of analyzing data, reducing data and concluding data. The application of discovery learning to science learning needs to prepare a problem/issue which is used as material for discussion by students. Supporting factors, namely the existence of infrastructure owned by complete schools and having teachers who are able to work well together for learning, teacher mastery of discovery learning models and being creative in innovating using learning media. The obstacles experienced were that the teacher could not control the classroom situation, the learning process was long and the location of the school was less strategic.